(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
‘Third-Eye Chakra’, also known as ‘Ajna Chakra’ in Sanskrit, is the sixth of the body’s seven major Chakras. It is also known as the "perception center" and, said to be the seat of soul and the portal to higher awareness. It is essential for achieving greater awareness and serves as the focus of concentration during Asana or meditation practices. Ajna Chakra corresponds to the hypothalamus, pituitary gland, and pineal gland, as well as the eyes, ears, and nose in the physical body. Vedic manas yoga is a holistic approach to yoga that integrates concepts from the Vedas, ancient Indian literature, with practices that attempt to balance the mind, body, and spirit. This study was conducted to develop the inner consciousness and awake the dormant powers of individual participants using Vedic manas yoga. In this observational study, a total 30 physically and mentally healthy subject aged in between 5 to 15 years of both gender from Patanjali Gurukulam, Haridwar, were included. The Pre- and Post-treatment SF-36 scores were statistically evaluated using paired t-test. There was a significant difference (p<0.5) observed in mean scores of Pre-program and Post-program scores of SF-36 after three days programmed interventions against psycho-social, spiritual and emotional development of subjects. The paired t-test revealed a significant score having p<0.05 for pre-program and post-program questionnaire responses. The maximum improvement was recorded to be 22% with overall third-eye activation. Vedic manas yoga practice has shown significant improvement in SF-36 among subjects participating in this study and, further studies are recommended to awaken the inner consciousness and align the energies of body, mind and spirit.